Patient-Reported Outcomes in Patients with Chronic Kidney Disease and Kidney Transplant—Part 1 - Tang, Evan; Bansal, Aarushi; Novak, Marta; Mucsi, Istvan (Frontiers in Medicine, 2018)
Chronic kidney disease is a complex medical condition that is associated with several comorbidities and requires comprehensive medical management. Given the chronic nature of the condition, its frequent association with psychosocial distress, and it’s very significant symptom burden, the subjective patient experience is key towards understanding the true impact of chronic kidney disease on the patients` life. Patient reported outcome measures are important tools that can be used to support patient-centered care and patient engagement during the complex management of patients with chronic kidney disease. The routine collection and use of patient reported outcomes in clinical practice may improve quality of care and outcomes, and may provide useful data to understand the disease from both an individual and a population perspective. Many tools used to measure patient reported outcomes focus on assessing health related quality of life, which is significantly impaired among patients with chronic kidney disease. Health-related quality of life, in addition to being an important outcome itself, is associated with clinical outcomes such as health-care use and mortality. In Part 1 of this review, we provide an overview of patient reported outcomes and implications of their use in the context of chronic kidney disease. In Part 2, we will review the selection of appropriate measures and the relevant domains of interest for patients with chronic kidney disease.